RETRACTED: Long Non-Coding RNA ELFN1-AS1 Promoted Colon Cancer Cell Growth and Migration via the miR-191-5p/Special AT-Rich Sequence-Binding Protein 1 Axis - Du, Yongjun; Hou, Yanmei; Shi, Yongbo; Liu, Juan; Li, Tingxin (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) are reported to participate in tumor development. It has been manifested in previous researches that lncRNA ELFN1-AS1 is involved in early-stage colon adenocarcinoma with potential diagnostic value. However, no studies have revealed the specific mechanism of ELFN1-AS1 in colon cancer, and there are no other studies on whether ELFN1-AS1 is associated with tumorigenesis. In our study, ELFN1-AS1 with high expression in colon cancer was selected by TCGA analysis, and the survival analysis was carried out to verify it. Subsequently, qRT-PCR was adopted for validating the results in tissues and cell lines. Cell counting kit-8 (CCK8), 5-ethynyl-2'-deoxyuridine (EdU), cell colon, cell apoptosis, cell cycle, cell migration, and invasion assays were utilized to assess the role of ELFN1-AS1 in colon cancer. Results uncovered that ELFN1-AS1 expression was prominently raised in colon cancer cells and tissues. ELFN1-AS1 decrement restrained cells to grow through interfering with distribution of cell cycle and promoting apoptosis. Meanwhile, ELFN1-AS1 decrement weakened the capacity of cells to migrate and invade. What's more, ELFN1-AS1 was uncovered to act as a competing endogenous RNA (ceRNA) to decrease miR-191-5p expression, thus raising special AT-rich sequence-binding protein 1 (SATB1), a downstream target of ceRNA. To sum up, ELFN1-AS1 drives colon cancer cells to proliferate and invade through adjusting the miR-191-5p/SATB1 axis. The above results disclose that lncRNA ELFN1-AS1 is possibly a novel treatment target for colon cancer cases.